Sikap Jepang Terhadap Korea Selatan Terkait Agreement On Comfort Women 2015 - Beti Regina Ratri (Jurnal Paradigma, 2019)
Jugun ianfu or comfort women is a term for women who were recruited by theJapanese Government during the Japanese military occupation in World War II which was used as a slave to sexual of Japanese military. The desire of the victims, especially in South Korea to get responsibility and justice rights for the treatment of Japanese military in the past, demanded that Japan respond to various demand. Japan has tried various responses in fulfilling demands, the one is Agreement on Comfort Women 2015 but there have been various criticisms and rejections of the response so that the problem of this issue cannot be resolved. This article aims to discuss how Japan responds to the demands of ex-comfort women in South Korea. The method used is library research and qualitative research.